Reseña histórica de la Gastroenterología y Endoscopía del aparato digestivo en el Perú: un reconocimiento a los gastroenterólogos que forjaron su desarrollo - Ramírez Ramos, Alberto (2018)
We present this brief historical article as recognition to Peruvian physicians who founded, developed, and still continue their hard work in gastroenterology and digestive endoscopy. This article summarizes personal experiences from three generations of gastroenterologists, so that the readers will have a chance to recognize the enormous sacrifice and dedication of colleagues working in this field, as well as their professional development and their contribution in the understanding and management of gastrointestinal pathology in Peru.